Some Principles Of Creative Training And Education Of Modern Youth - Umarov, Xabibulla; Goyibnazarov, Khabibulla (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
It is well known that the role of the teacher is very important in fostering creative abilities in young people. Here we encounter great difficulties, since in practice it turns out that secondary schools are not always provided with a sufficient number of talented teachers who are able to individually approach students and educate young people to think independently.